Cumulative Effects, their Causal Pathways and Social Impact Assessment: Lessons from Aotearoa New Zealand. - Taylor, C. Nicholas; Mackay, Michael (Environmental Management, 2025)
Cumulative effects result incrementally from a series of actions over time. On their own, the causative actions behind cumulative effects may be one-off and minor but become significant when they aggregate. Drawing on a practice example from Aotearoa New Zealand—the widespread expansion of irrigation over thirty years and associated land use changes—this paper extends our understanding of cumulative effects in several ways. First, the example shows that in Aotearoa New Zealand, the institutional and practice aspects of cumulative effects assessment are poorly developed, despite being required in legislation and recognized in case law. Part of the problem, we argue, is an unclear mandate for strategic environmental assessment that has limited the development of consistent cumulative effects assessment theory and practice. The "practice" element to improve, we suggest, is an integrated assessment of accumulating impact pathways, with particular implications for the conduct of social impact assessments. The key "institutional" improvement needed is a stronger role for strategic environmental assessment that incorporates social impact assessment, to address the social impacts of cumulative effects in advance, as well as for monitoring actual effects.